Construction waste estimation analysis in residential projects of Malaysia - Kupusamy, Kumanan; Nagapan, Sasitharan; Abdullah, Abd Halid; Kaliannan, Suaathi; Sohu, Samiullah; Subramaniam, Shivaraj; Maniam, Haritharan (Engineering, Technology and Applied Science Research (ETASR), 2019)
Construction and demolition (C&D) waste account for an oversized share of all solid waste generated worldwide. Statistical data confirm that, globally, 10-30% of waste originates from construction and demolition works. The types of waste from construction activities are wood, metals, concrete waste and mixed wastes. Waste generation continues to increase with the economy and population growth. A great challenge is providing more waste disposal facilities such as landfills to treat the waste. Rapid urbanization and insufficient attention to C&D waste generation, particularly in developing countries like Malaysia, have contributed to an urgent need for additional research on waste generation as there is a lack of information. The aim of this study is to predict the construction waste generation for the peninsular of Malaysia by quantifying construction waste generation data for Kuala Lumpur and to estimate the construction waste generation in 2016 for the peninsular of Malaysia. The estimation approach used was the proportion method with 20% of total sites in each state. Indirect waste measurement method was used to estimate waste generation. Total waste generation for Kuala Lumpur was around 6,101.46 metric tons. The predicted total amount of C&D waste generated for residential projects throughout Malaysia Peninsular is 63,101.93 metric tons. The initial prediction of construction waste generation for Malaysia Peninsular can be used as a baseline for future study.